Synthesis of Learning Styles and Learning Media to Optimize 21st Century Skills in Vocational Education: A Systematic Literature Review - Fahmi Anhar Muladi; Maria Paristiowati; Cecep Kustandi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This systematic literature review examines the relationship between learning styles and learning media in optimizing 21st-century skills among Diploma Three (D3) vocational students. Through systematic analysis of 74 relevant national and international journal articles published between 2018 and 2024 from Scopus database, this study reveals that the alignment between learning styles (visual, auditory, kinesthetic) and learning media significantly influences the development of critical thinking, creativity, communication, and collaboration skills. Technology-based media such as interactive videos, learning management systems (LMS), and virtual simulations effectively accommodate diverse learning preferences while enhancing students' motivation and engagement in the learning process. The findings indicate that e-modules integrating problem-based learning (PBL) demonstrate effectiveness rates of 65-85% in improving critical thinking skills. This research concludes that the integration of learning styles with digital-based learning media serves as an effective strategy to produce competent and adaptive vocational graduates who are well-prepared to face the challenges of Industry 4.0 and Society 5.0.